PERENCANAAN STRATEGIS DAN PENGELOLAAN SUMBER DAYA MANUSIA - DRS H Fuad (Jurnal Manajemen dan Bisnis, 2021)
This journal discusses about strategic planning and human resource management. It aims to know the definition, influencing factor, principle, used approach, the benefit of strategic planning and human resource management, and the relationship between planning and other management functions. Basically, strategic planning is the process of setting the basic missions and long-term goals of an organization or institution and a series of actions to achieve the set missions and goals. Planning becomes the basic for the other management functions so greatly affects the success of the series of overall management process. The strategic plan as long term plan were arranged after setting visions and missions and it is described in more detail in the operational plan. Strategic plan arrangement are affected by internal and external factors and based on the specific principles. In formulating strategies are necessary to use a sistematic approach. Generally, human resource planning process through four stages. They are collecting and analysis data, setting the goals and policies, designing the implementations of the plan, and designing the monitoring and evaluation systems. Human resource planning gives many benefits not only for human resource but also for sustainability of the organization. Planning related to job analysis, recruitment, selection, career planning, compensation, and training.